Make, learn, exhibit and share with others: The case of Inhibition - Koutsomichalis, Marinos (My University, 2025)
This article scrutinises an endeavour staging together hardware prototyping, co-design and exhibition-of/performance-with DIY artefacts. Inhibition pivots on a neural network controlled headset capable of electroencephalography and algorithmic audio composition. This technology is detailed and the particular ways in which it affords a multi-faceted doing-it-with-others are elaborated upon. Technological and artistic implications are discussed vis-à-vis: holistic frameworks for co-production/education; multi-modal affect; participatory/relational art; Dewean pragmatism; and the practice and culture of ‘open-sourcing’. It is shown that the values that are more often than not associated with art making fail do justice the ramifications of such an endeavour and that the latter cannot be thought of through an hylomorphic lenses. A different vector of values is demanded that rather concerns playful techno-scientific experimentation, ‘commonism’ and socio-material enactment. On this continuum, the author suggests neo-constructivism, democracy and post-selfhood as the lenses to think about Inhibition.